Kebutuhan Pengadopsian Praktik Akuntansi Syariah di Industri Halal: Studi Kasus Thailand - Tannia M. Juwana; Murniati Mukhlisin; Necdet Sensoy (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2025)
Investigate the significant development of halal industry and the urgent need for countries with Muslim minorities to adopt sharia accounting practices. The focus was on Thailand which was used as a representative of Muslim minority countries. Moreover, the method applied was a Systematic Literature Review using the PRISMA framework. This was achieved by retrieving and filtering different literature from Google Scholar based on certain inclusion or exclusion criteria followed by the conduct of a quality assurance test. The results showed that Thailand successfully dominated halal industry but Sharia accounting practices were rarely adopted. This gap has certain challenges and opportunities related to the integration of Sharia principles into halal industry. The observations were expected to provide a comprehensive analysis of the role of halal industry in advancing the adoption of Sharia accounting in Muslim minority countries.